Aerobic exercise, an effective intervention for cognitive impairment after ischemic stroke - Zhu, Mingjin; Chen, Wenjun; Zhang, Jie (Frontiers in Aging Neuroscience, 2025)
Cognitive dysfunction is a common and debilitating complication following ischemic stroke, significantly impairing the quality of life of patients. In recent years, aerobic exercise has emerged as a promising non-pharmacological intervention to mitigate post-stroke cognitive impairment (PSCI). This review synthesizes current evidence on the efficacy and mechanisms of aerobic exercise in enhancing cognitive recovery after ischemic stroke. Key mechanisms include improved cerebral hemodynamics through enhanced cerebral blood flow (CBF), promotion of neuroplasticity via brain-derived neurotrophic factor (BDNF)-mediated pathways, suppression of neuroinflammation (e.g., NLRP3 inflammasome inhibition), and attenuation of oxidative stress. Preclinical and clinical studies demonstrate that aerobic exercise modalities such as gait training, cycling, and aquatic therapy enhance cognitive domains including memory, executive function, and attention, with optimal benefits observed at moderate-to-high intensity and a frequency of ≥3 sessions per week. Despite robust evidence, challenges remain in standardizing exercise protocols and addressing individual variability in treatment response. Future research should prioritize large-scale randomized controlled trials to validate long-term cognitive benefits and identify biomarkers for personalized rehabilitation strategies. This review underscores the imperative to integrate aerobic exercise into post-stroke rehabilitation paradigms, offering a dual therapeutic approach to improve both physical and cognitive outcomes.